Is There a Catholic Sharing Ethic?: A Research Note - Rigney, Daniel (Sociology of religion, 2004)
Tropman (1995) and others have hypothesized the existence of a distinctively Catholic ethic centered on the values of community and sharing with others, in contrast to a Weberian Protestant ethic emphasizing individual achievement and self-reliance. This study evaluates the hypothesis empirically by examining Gallup and General Social Survey data reflecting self-reported volunteer service by religious affiliation. While these limited data on volunteerism m the United States do not corroborate the existence of a distinctively Catholic sharing ethic, they do point toward the need for further research on cultures of sharing in general, both religious and secular.